PHYSICOCHEMICAL, RHEOLOGICAL, AND SENSORY EVALUATION OF VOLUMINOUS BREADS ENRICHED BY PURSLANE (PORTULACA OLERACEA L.) - DELVARIANZADEH, M.; NOURI, L.; MOHAMMADI NAFCHI, A.; EBRAHIMI, H. (Italian Journal of Food Science, 2020)
Portulaca oleracea (purslane) can be used as a vegetable and herb for medical and food products. The aim of this study was to investigate the psychochemical, rheological, and sensory properties of voluminous breads enriched by different amounts of purslane powder (0, 5, 10, and 15%) were compared to a control group. The results showed that, with an increase in the concentration of Purslane in samples, water absorption capacity, stability under mixer, and softening level increased. Adding 15% of purslane powder decreased farinograph quality number significantly. Addition of purslane powder also improved resistance to extension and decreased extensibility, energy, and viscosity of the dough significantly. In terms of sensory properties, the sample with 15% purslane powder obtained the minimum score and other samples had acceptable conditions in terms of different sensory properties like taste, texture, color, odor, and general acceptability. In summary incorporation of purslane in voluminous bread is feasible and the optimum percentage of the purslane powder is 10% for the best acceptance in sensory evaluation.